2023
DOI: 10.1021/acs.organomet.3c00191
|View full text |Cite
|
Sign up to set email alerts
|

Hard to Handle: Extremely Labile Hydrido Nickel(II) Complexes of Cyclometalated CNN and NCN Ligands

Abstract: From the two organonickel(II) scaffolds [Ni(Phbpy)]+ and [Ni(PyPhPy)]+ (HPhbpy = 6-phenyl-2,2′-bipyridineHC∧N∧N and Py(HPh)Py = 2,6-di-2-pyridyl-benzeneN∧(HC)∧N) the hydrido complexes [Ni(C∧N∧N)H] and [Ni(N∧C∧N)H] were studied in a combined experimental/theoretical approach. The hydrido complexes were prepared via the reaction of the halido derivatives [Ni(C∧N∧N)X] and [Ni(N∧C∧N)X] (X = Cl, Br) with Li(Et3BH) (superhydride). The C∧N∧N complex undergoes rapid reductive elimination (RE) yielding HPhbpy and Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…[12,13] Rich redox properties combined with varying coordination geometries of the nickel center, as well as the rational design of the ligand environment for the metal coordination, confer specific catalytic properties to the nickel-based materials. [14][15][16][17] Furthermore, nickel is one of the few metals capable of efficiently catalyzing the reduction of CO 2 to hydrocarbons (C 1 -C 3 ), including methane. [18][19][20] The uniqueness of Ni-based catalysts can be attributed to the optimal combination between COand H 2 -producing catalysts, facilitating the activation of CO 2 and the subsequent hydrogenation of CO, that is, a crucial step in hydrocarbon formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Rich redox properties combined with varying coordination geometries of the nickel center, as well as the rational design of the ligand environment for the metal coordination, confer specific catalytic properties to the nickel-based materials. [14][15][16][17] Furthermore, nickel is one of the few metals capable of efficiently catalyzing the reduction of CO 2 to hydrocarbons (C 1 -C 3 ), including methane. [18][19][20] The uniqueness of Ni-based catalysts can be attributed to the optimal combination between COand H 2 -producing catalysts, facilitating the activation of CO 2 and the subsequent hydrogenation of CO, that is, a crucial step in hydrocarbon formation.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel is considered a suitable replacement for precious metals in developing catalysts for the electroreduction of CO 2 due to its wide valence range spanning from 0 to +4 [12,13] . Rich redox properties combined with varying coordination geometries of the nickel center, as well as the rational design of the ligand environment for the metal coordination, confer specific catalytic properties to the nickel–based materials [14–17] . Furthermore, nickel is one of the few metals capable of efficiently catalyzing the reduction of CO 2 to hydrocarbons (C 1 –C 3 ), including methane [18–20] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explore how this change in coordination environment affects the photophysical behavior of the isostructural Ni II complexes in Scheme 1b. A recent study reported that such changes of the coordination environments provided by different tridentate chelate ligands can greatly affect the stability and reactivity of the resulting Ni II complexes, but the influence on the excited state structure and the photophysics remains underexplored [34] . Here, we investigate how the Ni II complexes dissipate their excitation energy and how long‐lived luminescent 3 LC or 3 MLCT excited states similar to those encountered in many Pt II and Au III complexes can potentially be obtained in square‐planar Ni II compounds.…”
Section: Introductionmentioning
confidence: 99%